2012
DOI: 10.1001/archneurol.2011.892
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Classification of Volitional Functional Magnetic Resonance Imaging Responses in Patients With Severe Brain Injury

Abstract: Background: Recent neuroimaging investigations have explored the use of mental imagery tasks as proxies for an overt motor response, in which patients are asked to imagine performing a task, such as "Imagine yourself swimming." Objectives: To detect covert volitional brain activity in patients with severe brain injury using pattern classification of the blood oxygenation level-dependent (BOLD) response during mental imagery and to compare these results with those of a univariate functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 18 publications
2
47
1
Order By: Relevance
“…Previous neuroimaging studies have established that brain function can serve as a proxy for overt behavior in patients who are aware, yet unable to produce any overt physical responses (2)(3)(4)(5)(6)(7)(8)36). To date, these studies have relied on a response according to instruction, albeit a brain response, to establish that a significant minority of patients (∼19%) (6, 7) can follow commands and, in some cases, communicate with the outside world (2, 3, 7).…”
Section: Decoding Conscious Experiences In Behaviorally Nonresponsivementioning
confidence: 99%
“…Previous neuroimaging studies have established that brain function can serve as a proxy for overt behavior in patients who are aware, yet unable to produce any overt physical responses (2)(3)(4)(5)(6)(7)(8)36). To date, these studies have relied on a response according to instruction, albeit a brain response, to establish that a significant minority of patients (∼19%) (6, 7) can follow commands and, in some cases, communicate with the outside world (2, 3, 7).…”
Section: Decoding Conscious Experiences In Behaviorally Nonresponsivementioning
confidence: 99%
“…Several recent neuroimaging studies have demonstrated that, despite the apparent absence of external signs of consciousness, a significant small proportion of behaviorally nonresponsive patients with disorders of consciousness can respond to commands by willfully modulating their brain activity according to instruction. [7][8][9][10][11] Despite these advances, little is known about the mental life of such patients with regard to whether they can have any coherent thoughts. One fundamental mental function, critical for coherent thinking, is the ability to pay attention.…”
mentioning
confidence: 99%
“…Moreover, stronger signs of awareness were found through active paradigms, i.e. when the patient had to volitionally modulate his or her cerebral activity in response to specific instructions (Owen et al, 2006, Monti et al, 2010, Bardin et al, 2012, Naci and Owen, 2013, Vogel et al, 2013. A well-known example involves UWS or MCS patients who were asked to imagine either pursuing or stopping sedative infusions.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Monti et al (Monti et al, 2010), the authors suggest and advocate comparing similarities between the cerebral activations obtained during the communication tasks to those resulting from the explicit imagery tasks. However, this method has not been compared with other detection methods, such as analyses based on the use of support vector machines (Bardin et al, 2012). The efficacy of each method for detecting patterns of volitional activations must thus be explored and compared.…”
Section: Introductionmentioning
confidence: 99%